34PThe importance of p53 signaling pathway in the evolution of gastric cancer. (7th November 2019) - Gurzu, S; Sugimura, H; Van Staden, R I; Yamada, H; Jung, I
Abstract: Background: Although p53 pathway was previously explored in human carcinogenesis, the clinical implication of this gene is still unknown. The aim of this paper was to explore the particularities of TP53gene, at molecular and protein level, in gastric cancer. Methods: In 197 surgical specimens provided from patients with gastric carcinomas, consecutive cases with curative resection, without preoperative therapy, the clinicopathological parameters were correlated with immunohistochemical (IHC) expression of p53, HER-2 and the DNA mismatch repair protein MLH-1. Mutations in exons 2-11 of the TP53 were also screened using Sanger sequencing. Results: The rate of TP53 mutation was 28.43% (n = 56). Although it was a widely distribution among the exons 2 and 11 (except exon 9 which did not present mutations), in half of the cases mutations were located in the exons 5 (n = 13) and 8 (n = 15). No statistical correlations were seen between TP53 mutation rate and most of the clinicopathological parameters (e.g. age and gender, tumor localization, microscopic aspect, presence of intestinal metaplasia, HER-2 expression, overall survival). Compared to the non-mutated cases, those that showed mutations, independently from the involved exon, displayed more frequent p53 protein in over 50% of tumor cells (p = 0.004). Although no correlation with pT (p = 0.63) and pN stage (p = 0.84) was seen, a direct correlation was found with the Dukes-MAC-like staging system for gastric cancer, which was proposed by our team in 2017. Based on this system, a significant high number of cases diagnosed in stage pT3N1-3 showed TP53 mutation, whereas mutations were rare in pT3N0 cases and pT1-2 stage, independently from lymph node status (p = 0.03). Another significant correlation regarded the MLH-1 protein, which was more frequently (p = 0.01) negative in non-mutated versus mutated cases (19.86% vs 7.14%). Conclusions: As MLH-1 negativity is considered an indicator of microsatellite instability, the present study conclude that TP53 gene seems to not be involved in gastric cancers microsatellite instability pathway and do not iterract with HER-2 pathway. Occurrence of TP53 gene mutations induce overexpression of p53 protein in tumor cells and increases risk of lymph node metastases, especially in locally advanced cases. Legal entity responsible for the study: Romanian National Authority for Scientific Research, CNCS – UEFISCDI. Funding: Romanian National Authority for Scientific Research, CNCS – UEFISCDI, project number 20 PCCF/2018, code: PN-III-P4-ID-PCCF-2016-0006. Disclosure: All authors have declared no conflicts of interest.